Jailtacht : the Irish language, symbolic power and political violence in Northern Ireland 1972-2008 - Mac Giolla Chriost, Diarmait, 1965- (University Of Wales Press, 2012)
THIS BOOK TELLS THE DRAMATIC AND OFTEN SURPRISING STORY OF THE LEARNING OF THE IRISH LANGUAGE BY IRISH REPUBLICAN PRISONERS HELD IN THE INFAMOUS H-BLOCK CELLS DURING THE BLOODY POLITICAL CONFLICT IN NORTHERN IRELAND.